Summary and conclusions [In West African agriculture and climate change: A comprehensive analysis] - Jalloh, Abdulai; Faye, Mbène Dièye; Roy-Macauley, Harold; Sérémé, Paco; Zougmoré, Robert; Thomas, Timothy S.; Nelson, Gerald C. (International Food Policy Research Institute, 2013)
Climate variability is a reality that is affecting rural livelihoods in West Africa today and presenting a growing challenge in the region, as in many other parts of the African continent and elsewhere. Climate change will have far-reaching consequences for the poor and marginalized groups among which the majority depend on agriculture for their livelihoods and have a lower capacity to adapt. Weather-related crop failures, fishery collapses, and livestock deaths in addition to losses of property are already causing economic losses and undermining food security in West Africa. This situation is likely to become more desperate and to threaten the survival of the majority of poor farmers as global warming continues. Feeding the increasing populations in a subregion with one of the highest rates of population growth in the world requires radical transformation of a largely underdeveloped agriculture over the next four decades. A major challenge is increasing agricultural production among resource-poor farmers without exacerbating environmental problems and simultaneously coping with climate change.